WASP-186 and WASP-187: two hot Jupiters discovered by SuperWASP and SOPHIE with additional observations by TESS. Issue 1 (22nd September 2020) - Schanche, N; Hébrard, G; Collier Cameron, A; Dalal, S; Smalley, B; Wilson, T G; Boisse, I; Bouchy, F; Brown, D J A; Demangeon, O; Haswell, C A; Hellier, C; et al.
ABSTRACT: We present the discovery of two new hot Jupiters identified from the Wide-Angle Search for Planets (WASP) survey, WASP-186b and WASP-187b (TOI-1494.01 and TOI-1493.01). Their planetary nature was established from SOPHIE spectroscopic observations, and additional photometry was obtained from Transiting Exoplanet Survey Satellite. Stellar parameters for the host stars are derived from spectral line, infrared flux method, and isochrone placement analyses. These parameters are combined with the photometric and radial velocity data in a Markov chain Monte Carlo method to determine the planetary properties. WASP-186b is a massive Jupiter (4.22 ± 0.18  M J, 1.11 ± 0.03  R J ) orbiting a mid-F star on a 5.03-d eccentric ( e = 0.327 ± 0.008) orbit. WASP-187b is a low-density (0.80 ± 0.09  M J, 1.64 ± 0.05  R J ) planet in a 5.15-d circular orbit around a slightly evolved early F-type star.